Training possibilities in Europe - Organisation for Economic Co-operation and Development ([Paris : Organisation for Economic Co-operation and Development, 1962)
This edition represents an attempt to provide a concise listing of European training facilities in a single volume.
rpm 22/01/2019
Loans
Keywords: Professional education